An Effect of Time Management, Supervision, and Work Facilities on Employee Work Effectiveness at PT. Mekar Karya Mas - Saimara A.M Sebayang; Abdi setiawan; Tri yolanda (Budapest International Research and Critics University, 2022)
This study aims to determine the time management, supervision, and work facilities on the work effectiveness of employees at PT. Mekar Karya Mas. This study is a quantitative descriptive study with a sample of 35 respondents, while the sampling technique used in this study is census sampling. In this study, the independent variable consists of the influence of time management, supervision, and work facilities, while the dependent variable is work effectiveness. Testing the instrument using validity and reliability tests, while the data analysis method uses multiple linear regression analysis, t-test, f test, and R2 with the help of Statistical Product and Service Solution (SPSS) version 22. The results of the study of the independent time management variable (X1) obtained t-count - 2,790 > t-table 1,696, supervision variable (X2) t-count 1,976 > t-table 1,696, work facilities variable (X3) t-count 3,620 > t-table 1,696. Then the time management variable (X1) has a partial negative effect on work effectiveness (Y), the supervision variable (X2) has a partially positive effect on work effectiveness (Y), and the work facilities variable (X3) has a partial effect on work effectiveness. The results of the f test show that f-count 6.816 > f-table 2.91, while the significance is 0.001 < alpha at a significant level of 0.05, which means that the independent variables (time management, supervision, and work facilities) simultaneously or simultaneously affect the dependent variable (effectiveness) work) positively and significantly.